Two new species of quill mites (Acari: Syringophilidae) associated with the Chestnut-fronted Helmetshrike Prionops scopifrons (Peters) (Passeriformes: Vangidae) in Kenya - Klimovičová, Miroslava; Skoracki, Maciej; Hromada, Martin (Zootaxa, 2016)
Two new species of syringophilid mites collected from Prionops scopifrons (Peters) (Passeriformes: Vangidae) in Kenya are described: Neoaulonastus prionops sp. nov. and Picobia meru sp. nov. They are the first syringophilid records from birds of the family Vangidae.